Webquest: uma proposta metodológica para as aulas de língua portuguesa - Cavalcanti, Maria Patrícia Pereira (2016)
Thanks to the contemporary environment permeated by digital devices, the school needs to state its place before this proposition of technological innovations. In view of this context, this dissertation presents results of a methodological intervention of Internet research with 8th grade students in a municipal school located in Rio Tinto-PB. The present study aimed to develop research, reading and textual production skills through the webquest's investigative and targeted methodological proposal. In order to do so, we betook Gabriel's contributions (2013) in the aspects that highlight the digital revolution in education, by Lévy (1996, 1999) with approaches regarding cyberculture, by Moran (2012) and by Moran, Masetto and Behrens (2013) ant their contribution on education and on the challenges proposed by the changes brought along with the digital era, by Ribeiro (2012) due to the technological resources in the classroom, by Coscarelli and Ribeiro (2014) in the approaches to studies on digital literacy, by Santaella (2009) focusing on the types of readers, highlighting the immersive reader of Xavier (2010) and Coscarelli (2012) with the perspective of hypertext studies, among others. We carried out the investigative procedure through ethnographic and netnographic processes, for we believe that these processes contributed to the study of the culture and the social situation in which the research participants are inserted, as well as their behavior in a digital environment. The results point to the contribution regarding digital literacy – since it develops reading and textual production skills with a digital support – as well as to the dynamism of the teaching / learning process through internet-oriented research. In the current circumstances, it is necessary to approach this theme because it is of great relevance to the social and cultural chaining and to bring the role of digital technologies in education to the discussion.